Despoluição de um lago - progressão geométrica - Chiconato, Daniele Cristina (2013)
This work aims to assist the Geometric Progression Content Learning, developing educational material supported by research methodology called didactic engineering. We developed an instructional sequence based on a problem situation, in which students, by providing a simulation of a polluted river, should predict the time needed for the de-pollution to occur and develop a mathematical model in order to explain this phenomenon. The work was applied in a Ninth Grade classroom (Junior High School) in the State School called Victor Maida in Ibitinga with 29 students divided into trios. These trios remained together until the end of the application of the instructional sequence, which lasted five days. The sequence contained about 60 questions, which were formulated into a form with which the student could act autonomously, with minimal teacher intervention. Finally, this work was based on the collection of results in the analysis of priori and a posteriori of the responses provided by the teams, in order to check the results obtained.